Tectofugal and thalamofugal: a proposal for longitudinal studies in goose behaviour - Boyd, Hugh (Wildfowl, 1998)
The value of the comparative method in ethology was established at the intra- and inter-generic level about 60 years ago. Here I suggest that intraspecific comparisons of behaviour at long intervals may also be instructive (though in less dramatic ways) and discuss some of the difficulties in promoting and carrying out intergenerational research projects, using studies of geese as examples.